CHARACTERISTICS OF DEPRESSIVE DISORDERS IN PATIENTS WITH CROHN’S DISEASE TREATED AT THE GASTROENTEROLOGY AND HEPATOLOGY CENTER, BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics of depressive disorder in patients with Crohn’s disease treated at the Gastroenterology and Hepatology Center, Bach Mai Hospital. Subjects and methods: A cross-sectional descriptive study was conducted on 147 patients with Crohn’s disease examined and treated at the Gastroenterology and Hepatology Center, Bach Mai Hospital, from September 2025 to September 2026. Results: The mean age was 29.38 ± 11.1 years. Male patients accounted for 57.1% and females 42.9%, with a male-to-female ratio of 4:3. The prevalence of depression was 32%. The most common symptoms included depressed mood (97.9%), reduced energy (95.7%), loss of interest or pleasure (63.8%), loss of appetite (83%), and impaired concentration (48.9%). Mild depression accounted for 42.6% of cases, moderate depression for 40.4%, and severe depression for 17%.Conclusion: Depression in patients with Crohn’s disease was commonly observed in young individuals under 40 years old, predominantly at mild and moderate severity (83%).
Keywords: Depressive disorder, Crohn Disease, clinical characteristics.